PENGARUH STRATEGI PEMBELAJARAN PEER TUTORING TERHADAP HASIL BELAJAR PEMAHAMAN KONSEP - Fajariati Herina Putri; Lilik Anifah; I Gusti Putu Asto Buditjahjanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to determine the effect of the Peer Tutoring learning strategy on students' conceptual understanding. Peer tutoring is a learning strategy in which students teach and assist their classmates in understanding the material being taught. This research was conducted at SMKN 1 Lamongan with a sample of tenth-grade students divided into two groups: the experimental group, which implemented the Peer Tutoring strategy, and the control group, which followed learning without peer tutoring. The results of the study show that there is a difference in conceptual understanding among students who used the Peer Tutoring strategy, as evidenced by higher learning achievement. This indicates that the Peer Tutoring strategy is effective in enhancing students' conceptual understanding. Through peer interaction and teaching, students become more actively engaged in understanding the material and can explain concepts to one another in a way that is easier to comprehend. This study concludes that the implementation of Peer Tutoring can be an effective alternative for improving learning outcomes, especially in enhancing students' conceptual understanding of the subject matter.